iPad in education for dummie - Gliksman, Sam (John Wiley & Sons, 2015)
The iPad is a natural fit for education in the 21st century, and this hands-on guide shows you just how to implement it in your educational institution. iPad in Education For Dummies serves as a roadmap for the device's successful use as an education tool—from both a personal and institutional perspective. It examines why the iPad is a perfect fit for contemporary educational needs, how to purchase and deploy them within an organization, and outlines best practices, tools, and apps for their educational use across all curricula and grade levels.